Digital Leadership of School Administrators in Network for Enhancing Educational Management Efficiency Group 4, Under the Pathum Thani Primary Educational Service Area Office 1 - จุ้ยแจ้ง อนงค์นาถ; ชวศิริกุลฑล นันทนา; รักษนคร กุลจิรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to 1) examine the level of digital leadership of school administrators; 2) compare the digital leadership of school administrators; and 3) explore guidelines for developing digital leadership among school administrators within Network 4 of the Educational Management Efficiency Enhancement Group under the Pathum Thani Primary Educational Service Area Office 1. The sample consisted of 203 participants, including school administrators and teachers. A five-point rating scale questionnaire was employed as the research instrument, with an Index of Item-Objective Congruence (IOC) ranging from 0.80 to 1.00 and a reliability coefficient of .98. The statistical methods used for data analysis included frequency, percentage, mean, standard deviation, t-test, and F-test. Pairwise comparisons were conducted using Scheffé’s method, and content analysis was applied for qualitative data. The research findings revealed that: • The overall level of digital leadership among school administrators was at a high level. When considering each aspect, all dimensions ranged from high to the highest. • The comparison of digital leadership among school administrators showed that differences in position did not result in significant differences overall. However, differences in educational level resulted in statistically significant differences at the .01 level. Differences in work experience showed no significant differences overall or in each aspect. Differences in school size resulted in statistically significant differences at the .01 level. 3. The guidelines for developing digital leadership among school administrators comprised five key dimensions: digital communication, digital vision, fostering a digital learning culture, digital literacy, and digital citizenship. These guidelines emphasized the formulation of clear digital visions and strategies aligned with the school context, alongside fostering an organizational culture of learning in the digital era. They also highlight the importance of promoting participation and enhancing technological competencies among teachers and personnel, utilizing creative digital communication to support flexible management, and adhering to ethical principles in the use of data and technology to drive schools toward excellence amid digital transformation.